2012
DOI: 10.1016/j.biotechadv.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Arachis genomics for peanut improvement

Abstract: Peanut genomics is very challenging due to its inherent problem of genetic architecture. Blockage of gene flow from diploid wild relatives to the tetraploid; cultivated peanut, recent polyploidization combined with self pollination, and the narrow genetic base of the primary genepool have resulted in low genetic diversity that has remained a major bottleneck for genetic improvement of peanut. Harnessing the rich source of wild relatives has been negligible due to differences in ploidy level as well as genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
232
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(240 citation statements)
references
References 107 publications
(95 reference statements)
3
232
1
4
Order By: Relevance
“…Polymerase chain reaction was performed with the 53 SSR-based primers as described by Pandey et al (2012b). The reaction was conducted in a 10 µl reaction volume containing 5 ng of genomic DNA, 0.5 µmoles of each primer, 1.0 µl 10X PCR buffer, 0.25 mM of each dNTPs, 2 mM MgCl2 and 1.0 U Taq DNA Polymerase (Sib enzyme, Russia).…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…Polymerase chain reaction was performed with the 53 SSR-based primers as described by Pandey et al (2012b). The reaction was conducted in a 10 µl reaction volume containing 5 ng of genomic DNA, 0.5 µmoles of each primer, 1.0 µl 10X PCR buffer, 0.25 mM of each dNTPs, 2 mM MgCl2 and 1.0 U Taq DNA Polymerase (Sib enzyme, Russia).…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…Advances in other marker types, such as randomly amplified polymorphic DNA (RAPD) (Halward and Stalker, 1991;Halward et al, 1992), restriction fragment length polymorphism (RFLP) (Halward and Stalker, 1991;Kochert et al, 1996;Burow et al, 2009), amplified fragment length polymorphism (AFLP) (Herselman et al, 2004), simple sequence repeat (SSR) (He et al, 2003;Gimenes et al, 2007;Cuc et al, 2008;Liang et al, 2009), sequence-related amplified polymorphism (SRAP) , single strand conformational polymorphism (SSCP) (Nagy et al, 2010), and single nucleotide polymorphism (SNP) (Nagy et al, 2012), soon replaced the early exploration with proteins. During the past two decades, much effort has been made to develop genetic and genomic tools in cultivated peanut, such as construction of BAC libraries (Yuksel and Paterson, 2005;Guimarães et al, 2008), cDNA libraries (Luo et al, 2005;Proite et al, 2007;Guo et al, 2008Guo et al, , 2009Koilkonda et al, 2012), RNAseq using next generation sequencing technology (Guimaraes et al, 2012;Zhang et al, 2012) and development of DNA markers (see reviews of Feng et al, 2012;Pandey et al, 2012;Zhao et al, 2012; (Table 1). Among the various molecular markers investigated to date, simple sequence repeats (SSR) have emerged as one of the preferred DNA marker system for conducting genetic and genomic studies in cultivated peanut.…”
Section: Recent Development In Molecular Markersmentioning
confidence: 99%
“…To date, 15,518 SSRs have been developed by various research groups, although some are likely to be redundant (Table 1). Several reviews have recently summarized progress in peanut genetics and genomics tool and resource development (see reviews of Feng et al, 2012;Pandey et al, 2012;Zhao et al, 2012. Feng et al (2012) reported on EST progress and application (Fig.…”
Section: Recent Development In Molecular Markersmentioning
confidence: 99%
See 2 more Smart Citations